A Linguistic Analysis of Istifhām and Tasybīh as Rhetorical Strategies in the Qur’an: Tinjauan Linguistik atas Istifhām dan Tasybīh sebagai Strategi Retoris dalam Al-Qur’an - Pendi Nurul Azmi; Fikri Fillaili; Wildan Taufiq; Edi Komarudin (Senarai: Journal of Islamic Heritage and Civilization, 2025)
The Qur’an, as the holy book of Islam, not only contains guidance for life but also possesses a rich and sophisticated literary style. Two of the rhetorical devices frequently found in the Qur’an are istifhām (interrogation) and tasybīh (simile). This study aims to analyze the use of istifhām and tasybīh in the Qur’an from the perspective of the science of balāghah, as well as to uncover the beauty of their meanings and the rhetorical effects they produce. This study employs a qualitative-descriptive approach using content analysis on verses containing istifhām and tasybīh. The findings reveal that istifhām in the Qur’an does not always signify a question but is frequently used for negation, affirmation, instruction, and shifting attention, depending on the verse’s context. Meanwhile, tasybīh is used to concretize abstract meanings, reinforce moral messages, and form a strong aesthetic imagination in the reader’s mind. This study affirms that a deep understanding of rhetorical devices such as istifhām and tasybīh is crucial for grasping the more complete divine meanings and messages in the Qur’an